Change in central cardiovascular function in response to intense interval training: a systematic review and meta-analysis - Astorino, T. A.; Causer, E.; Hazell, T. J.; Arhen, B.; Gurd, B. J. (Medicine & Science in Sports & Exercise, 2022)
Introduction High-intensity interval training and sprint interval training significantly increase maximal oxygen uptake (VO_2max), which enhances endurance performance and health status. Whether this response is due to increases in central cardiovascular function (cardiac output (CO) and blood volume) or peripheral factors is unknown.